PENGEMBANGAN KARTU BULLYING “DIKTA” BERBASIS AUGMENTED REALITY PADA MATA PELAJARAN BIMBINGAN KONSELING SMA BBS BOGOR - Purnama, Happy Yoga; Wicaksono, Dirgantara (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2025)
Cyberbullying remains a significant concern in school environments. This study aimed to design and implement “DIKTA” Bullying Cards using Augmented Reality (AR) as an alternative learning medium to help students at SMAIT BBS Bogor understand various forms of bullying and improve their awareness and competence. The research adopted a Research and Development (R&D) approach using the ASSURE model, which involved needs analysis, prototype development, expert validation, and a pretest–posttest trial with Grade XI students. Findings from the large-scale trial indicated notable improvement. The average pretest score was 45.83, below the minimum mastery criteria (MMC), while the posttest average rose to 80.67, surpassing the MMC. The percentage of students achieving the MMC increased from 26.67% to 83.33%, with a learning gain of 76.02%, demonstrating the effectiveness of the media. Expert validation scores were 3.75/4 for media and 3.80/4 for content, indicating high validity. A few students showed score declines due to external factors such as focus and media adaptation. In conclusion, the DIKTA AR cards are valid, feasible, and effective for learning about cyberbullying. The media received positive student responses and is recommended for integration into school counseling programs.